The fall in German unemployment: A flow analysis - Carlos Carrillo-Tudela; Andrey Launov; Jean-Marc Robin (University of Kent, School of Economics, 2018)
In this paper we investigate the recent fall in unemployment, and the rise in part-time work, labour market participation, inequality and welfare in Germany. Unemployment fell because the Hartz IV reform induced a large fraction of the long-term unemployed to deregister as jobseekers and appear as non-participants. Yet, labour force participation increased because many unregistered-unemployed workers ended up accepting low-paid part-time work that was offered in quantity in absence of a universal minimum wage. A large part of the rise in part-time work was also due to the tax benefits Hartz II introduced to take up a mini-job as secondary employment. This has provided an easy way to top-up labour income staggering under the pressure of wage moderation. The rise in part-time work led to an increase in inequality at the lower end of income distribution. Overall we find that Germany increased welfare as unemployment fell.
Keywords: J21; J31; J63; J64; 330; Unemployment; part-time work; mini-jobs; non-participation; multiple job holding; income inequality; Germany; Hartz reforms